急性放射線性腸炎の1例 - 箕輪 慎太郎; 齋藤 大祐; 岡部 直太; 佐藤 太龍; 池崎 修; 三井 達也; 三浦 みき; 櫻庭 彰人; 林田 真理; 徳永 健吾; 戸成 綾子; 望月 眞; et al. (JOURNAL OF THE KYORIN MEDICAL SOCIETY, 2018)
Acute radiation enteritis is often self-limiting and reversible as long as radiotherapy ceases within a short period. Colonoscopy is thus rarely performed and the endoscopic findings have not been fully investigated. We encountered a case of acute radiation enteritis in which colonoscopy was performed. The patient was a 68-year-old man with prostatic cancer under hormone therapy. Back pain due to metastasis to the pelvic area developed, and radiotherapy was adopted. However, watery diarrhea began 4 days after the initiation of radiotherapy. Colonoscopy revealed mucosal erythema, edema, and epithelial friability with mucus adhesion in the sigmoid colon. Biopsied specimens showed shedding of superficial epithelium, atrophy of crypts, and infiltration of inflammatory cells into the lamina propria. On the basis of endoscopic and histopathological findings as well as the clinical pictures, acute radiation enteritis was diagnosed. Symptoms gradually improved after radiotherapy was suspended. Follow-up colonoscopy confirmed recovery to normal-appearing intestinal mucosa. When symptoms suggestive of colitis develop shortly after initiating radiotherapy, colonoscopy together with histopathological examination should be actively performed to achieve definitive diagnosis of acute radiation enteritis. 急性放射線性腸炎は自制内であり放射線治療の終了とともに改善することが多い。このため大腸内視鏡検査が行われることは稀であり，その内視鏡所見が詳細にまとめられた報告はない。今回，急性放射線性腸炎で大腸内視鏡検査を施行した一例を経験した。症例は前立腺癌に対するホルモン療法中であった68歳の男性である。骨盤転移による腰痛が出現し，放射線治療が開始された。治療4日後から水様性の下痢が始まり，大腸内視鏡検査を施行したところ，S状結腸の粘膜は発赤し浮腫状で，易出血性であり，粘液も付着していた。生検による病理組織では，表層上皮が脱落し陰窩は萎縮，また粘膜固有層に炎症細胞浸潤が認められた。臨床経過と内視鏡および病理組織所見より急性放射線性腸炎と診断した。放射線治療の中止により症状は次第に改善し，中止14日後の大腸内視鏡検査でも正常粘膜に復していることを確認した。放射線治療の開始後早期に腸炎症状が出現した時は，病理組織学的検査を含む大腸内視鏡検査を積極的に行い，急性放射線性腸炎の確定診断に努めるべきである。